Legionella spp. as causal agent of pneumonia - Lisette Sandrea-Toledo; América Paz-Montes; Alisbeth Fuenmayor-Boscán; Eyilde Piña-Reyes; Yeiny ívila-Roo; Morella Nava-Díaz (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2015)
Legionella species are recognized worldwide as important etiologic agents of pneumonia. In Venezuela the incidence is unknown. The purpose of this study was to standardize and implement methodologies (culture and Urinary Antigen) in our environment detect the presence of Legionella spp. in patients with suspected pneumonia who attended the emergence of adults at the University Hospital of Maracaibo (SAHUM). To do this, 75 samples of urine and sputum were studied. Sputum was cultured on selective and nonselective media for Legionella. Specific urinary antigen Legionella pneumophila serogrupo 1 was determined, by rapid immunochromatographic technique (Binax Now®). In cultured sputum samples, only one (1.33%) was positive and 7 (9.33%) were positive urine samples. Standardized methodologies used in this investigation showed high sensitivity and allowed the implementation of these methodologies in the Laboratory of Bacteriology Reference.